1999
DOI: 10.1074/jbc.274.23.16198
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Direct Repeat 3 Vitamin D3and Direct Repeat 4 Thyroid Hormone Signaling Pathways by the Human TR4 Orphan Receptor

Abstract: In situ hybridization analysis demonstrated that abundant testicular orphan receptor (TR4) transcripts were detected in kidney, intestine, and bone, which are vitamin D 3 target organs. Cell transfection studies also demonstrated that the expression of the vitamin D 3 target gene, 25-hydroxyvitamin D 3 24-hydroxylase, can be repressed by TR4 through high affinity binding (K d ‫؍‬ 1.32 nM) to the direct repeat 3 vitamin D 3 receptor response element (DR3VDRE). This TR4-mediated repression of DR3VDRE is in contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 42 publications
0
50
0
Order By: Relevance
“…TR4 is a transcriptional factor that recognizes the DNA element composed of the direct repeat (DR) motif located regulatory regions of its target genes, including DR-3 [8]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TR4 is a transcriptional factor that recognizes the DNA element composed of the direct repeat (DR) motif located regulatory regions of its target genes, including DR-3 [8]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro data suggest that TR4 functions as a master regulator to modulate many signaling pathways, including induction of the ciliary neurotrophic factor alpha [5, 6], interfering with retinoic acid receptor/retinoid X receptor [7], thyroid receptor [8], androgen receptor [9], and estrogen receptor-mediated pathways [10], and facilitating viral infection and propagation of HPV-16 and SV40 [11]. Mice lacking Tr4 ( TR4KO ) have high rates of early postnatal mortality, show significant growth retardation [12], display reproductive defects in both genders [12, 13], abnormalities in spermatogenesis [14], reduced lipoprotein metabolism [15, 16], and reduced gluconeogenesis [17], as well as defects in cerebella development [18].…”
Section: Introductionmentioning
confidence: 99%
“…A common characteristic of various nuclear receptors is that they play roles as functional regulators of other nuclear receptors since several nuclear receptors use a common response element for the regulation of target gene expression (Lee et al, 1997; Lee et al, 1999). These suggest that mutual regulation between nuclear receptors in the intracellular environment of adipocytes may lead to control adipocyte development and lipid homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Testicular orphan nuclear receptor 4 (TR4; Nr2c2), a member of the nuclear receptor superfamily, is able to regulate the expression of target genes through binding to direct repeats (DRs) of AGGTCA core motifs with variable numbers of spacer nucleotides (Kim et Lee et al, 1999). Several studies suggested that TR4 may play key roles in glucose and lipid metabolism (Liu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Perilipin, a lipid-droplet associated protein, coats lipid droplets in differentiating adipocytes and restricts the access of cytosolic lipases to lipid droplets, resulting in promotion of triacylglycerol storage (Brasaemle et al, 2000). Early studies have shown that TR4 could modulate gene expression via binding to DR1 element although TR4 has broad affinity for variable DRs with different spacer sequences from 0 to 6 nucleotides (DR0-DR6) (Lee et al, 1995; Lee et al, 1997; Lee et al, 1999). Here, we show that TR4 regulates perilipin gene expression through DR1 element (Plin-TR4RE) located in the perilipin promoter.…”
Section: Discussionmentioning
confidence: 99%